Novel graphite-carbon encased tungsten carbide nanocomposites by solid-state reaction and their ORR electrocatalytic performance in alkaline medium. (20th August 2015) - Huang, K.; Bi, K.; Xu, J.C.; Liang, C.; Lin, S.; Wang, W.J.; Yang, T.Z.; Du, Y.X.; Zhang, R.; Yang, H.J.; Fan, D.Y.; Wang, Y.G.; et al.
Graphical abstract: Abstract: Novel nanocomposites of spherical graphite-carbon encased tungsten carbide (GC-WC) are synthesized by solid state reaction with melamine and WO3 as precursors under N2 atmosphere. The diameters of the GC-WC composites range from 50 to 200 nm and the WC nanoparticles inside with an average size of ca. 15 nm distribute uniformly. The characterization results indicate that the GC-WC is composed of few layers of graphite carbon and WC nanoparticles with high crystallization and purity. Moreover, the electrocatalytic performance of GC-WC for the oxygen reduction reaction (ORR) in alkaline medium is further investigated by cyclic voltammetry (CV), rotating disk electrode (RDE) and chronoamperometry test with or without 3 M methanol. The results show that GC-WC has a considerable performance for ORR in the view of activity, stability and methanol tolerance, which may further used as proper supports for noble-metal based ORR catalysts in alkaline fuel cell. The synergetic interaction between the carbide nanoparticles and graphite carbon, which means that the surface graphite carbon layers are activated by WC nanoparticles for ORR and in turn protect inner WC from highly oxidizing environments has also been verified.